Nilai Pendidikan di Era Automasi: Implikasi Etis untuk Pendidikan Karakter Berbasis Islami - Luthfiatul Udhma; Abidatil Qinni; Ari Abi Aufa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The era of automation has brought profound changes to the educational landscape through the integration of intelligent technologies, artificial intelligence, and digital systems that increasingly shape learning processes. This transformation not only affects the interaction patterns between educators and learners but also shifts foundational educational values and introduces significant ethical challenges. In the context of Islamic education, these changes require a reformulation of relevant educational values to preserve learners’ moral and spiritual integrity. This study aims to analyze Islamic educational values in the age of automation and examine their ethical implications for strengthening character education. Through a comprehensive literature-based approach, the study finds that values such as amanah (trustworthiness), adl (justice), ihsan (excellence), mas’uliyyah (accountability), and mujahadah (perseverance) serve as essential instruments in building learners’ character so they can use technology wisely and responsibly. Furthermore, the study emphasizes that automation demands the integration of digital literacy and Islamic moral literacy to prevent dehumanization, digital plagiarism, technology dependence, and the decline of spiritual awareness. The findings indicate that character education grounded in Islamic values provides a strong ethical framework for addressing emerging moral risks in the digital era. Therefore, curriculum reconstruction, strengthening the role of educators as “digital murrabbi,” and the proportional use of technology aligned with maqāṣid al-syarī‘ah are required. This research contributes by offering a comprehensive Islamic ethical perspective as a foundational framework for the development of character education amid the rapid and inevitable acceleration of automation.